Unmasking the Loyal Maidservant in Germinie Lacerteux - Rushton, Jessica (MuseMedusa, 2022)
This article argues that by unmasking the secret life of the fictional maidservant, Germinie Lacerteux, the Goncourt brothers develop and describe a nineteenth-century social imaginary of the rebellious female servant. The rebellious maidservant emerges in the nineteenth-century social imagination through an interconnected web of discourses emanating from the period’s literature, faits divers, household manuals and criminology reports. By analysing Germinie Lacerteux in conjunction with nineteenth-century household manuals, this article explores how the Goncourts contributed to this interconnected web of discourses that created the nineteenth-century cultural stereotype of the rebellious female servant. In revealing the ‘true’ nature of the maidservant in their novel, the Goncourts imply that the bourgeoisie must learn to see the image of the devoted servant as nothing more than a construct in the social imagination. The guardian angel whom the bourgeoisie sought to hire is a myth born out of their increasing fears surrounding the potentially dangerous stranger in their home.